Preparation strategy of hydrogel microsphere and its application in skin repair - Chi, Honggang; Qiu, Yunqi; Ye, Xiaoqing; Shi, Jielin; Li, Ziyi (Frontiers in Bioengineering and Biotechnology, 2023)
In recent years, hydrogel microsphere has attracted much attention, which has shown great potential in the field of skin repair. The paper reviewed the recent progress in the preparation strategy of hydrogel microsphere and its application in skin repair. In this review, several preparation methods of hydrogel microsphere were summarized in detail. Besides, the related research progress of hydrogel microspheres for skin repair was reviewed, which was focused on the application of bioactive microspheres, antibacterial microspheres, hemostatic microspheres, and hydrogel microspheres as delivery platforms (hydrogel microspheres as microcarrier of drugs or bioactive factors or cells) in the field of skin repair. Finally, the limitations and future prospects of the development of hydrogel microspheres and its application in the field of skin repair were presented. It is hoped that the review could provide a valuable reference for the development of the preparation strategy of hydrogel microspheres and promote application of hydrogel microspheres in skin repair.